Analisis Gangguan Akses FTTH Layanan Internet PT. Circlecom Nusantara IndonesiaWilayah Pantai Indah Kapuk - Wicaksono, Burhan; Fajri, Annur (LPPM STMIK Antar Bangsa, 2024)
PT Circlecom Nusantara Indonesia is a private company engaged in information and communication technology services as an Internet Service Provider (ISP) with its product called Circleone. In providing services to its customers, PT Circlecom Nusantara Indonesia uses a fiber optic transmission network which is currently widely used by ISP providers in Indonesia to support their retail business. Fiber optic transmission networks are chosen to be more widely used by ISP providers because they have the ability to transmit information with large capacities in the digitalization era and support the use of FTTH (Fiber To The Home) technology. In providing services, of course, it will experience a network disturbance that needs to be analyzed to determine the type of disturbance, the cause of the disturbance and the solution. In this research, the author will analyze these things on the fiber optic network with FTTH technology provided by PT Circlecom Nusantara Indonesia in Pantai Indah Kapuk (PIK) area. The results of the study found the fact that FTTH technology network interference with optical fiber experienced by PT Circlecom Nusantara Indonesia customers in Pantai Indah Kapuk (PIK) area is strongly influenced by the attenuation value of optical fiber where the maximum lower value of optical fiber power link budget attenuation of -28 dBm causes network interference that is felt directly by customers.